Performance of Warsaw Stock Exchange Listed Family Companies during and after COVID-19 - Pawel PERZ (Communications of International Proceedings, 2023)
Most empirical studies indicate superior performance by family firms compared with non-family firms. This is mainly due to the reduction of agency costs, and the long-term orientation of the company's owners, which is conducive to conducting an optimal investment policy, a prudent debt policy, and a coherent value system. An interesting research problem is the analysis of the behavior of family and non-family businesses in the conditions of the crisis caused by the COVID-19 pandemic. The paper investigates the performance of family and non-family firms listed on the Warsaw Stock Exchange from 2019 to 2022. It was found that family firms substantially outperformed non-family firms during the crisis. Further analysis indicates that family firms with a higher SFI indicator (Substantial Family Influence indicator) performed better than other family firms, which suggests that higher family ownership and family involvement in management plays an important role in family firms’ economic resilience.
Keywords: family firms; performance; COVID-19